The Influence of Good Corporate Governance and Firm Size on Earning Management in Automotive Companies Listed on the IDX in 2019 - 2023 - Khanif, Alfin Nazlil; Sutarni, Sutarni (CV. Civiliza Publishing, 2025)
This study aims to examine the effect of good corporate governance on earnings management; the effect of firm size on earnings management; and the combined effect of good corporate governance and firm size on earnings management in automotive companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. This research adopts a quantitative approach, with data collected through documentation of financial reports from companies that meet the purposive sampling criteria. The data were analyzed using multiple linear regression with the assistance of SPSS version 26. The results indicate that good corporate governance has a positive and significant effect on earnings management; firm size has a negative and significant effect on earnings management; and good corporate governance and firm size simultaneously have a significant effect on earnings management in automotive companies listed on the Indonesia Stock Exchange during the 2019–2023 period.